ASPEK FEMINISME RADIKAL TOKOH DEWI AYU DALAM NOVEL CANTIK IU LUKA KARYA EKA KURNIAWAN - Fitri Mirnayanti; Sumiharti Sumiharti; Harbeng Masni (Universitas Batanghari, 2021)
This study aims to describe and document the radical feminism of Dewi Ayu in the novel Cantik Itu Luka by Eka Kurniawan. This research uses qualitative descriptive research methods, solving problems in a study by describing or describing and interpreting objects in the form of symptoms or social events in human life following the original. The results of the study covered aspects of feminism. There are 37 citations. Citations related to Physical Violence against Women there are ten quotes, Quotes related to the Exploitation of Women there are 20 quotes, Quotes related to the Role of Women of the character Dewi Ayu in the novel there are seven quotes. Based on the study results, it can be concluded that there are 37 excerpts of radical feminism studies in the novel Cantik Itu Luka by Eka Kurniawan, and the most dominant aspect in this study is the aspect of Exploitation of Women with 20 Citations.Keywords: analysis, radical feminist, novel